How to forget : a daughter's memoir - Mulgrew, Kate, 1955- (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"In this profoundly honest and examined memoir about returning to Iowa to care for her ailing parents, the star of Orange Is the New Black and New York Times bestselling author of Born with Teeth takes us on an unexpected journey of loss, betrayal, and the transcendent nature of a daughter's love for her parents"--